PARTIAL MELTING OF SPINEL LHERZOLITE IN THE SYSTEM CAO-MGO-AL2O3-SIO2 ± K2O AT 1·1 GPA - Liu X.; O'Neill H.St.C. (My University, 2004)
The compositions of multiply saturated partial melts are valuable for the thermodynamic information that the contain, but are difficult to determine experimentally because they exist only over a narrow temperature range at a given pressure. Here we try a new approach for determining the composition of the partial melt in equilibrium with olivine, orthopyroxene, clinopyroxene and spinel (Ol + Opx + Cpx + Sp + Melt) in the system CaO-MgO-Al2O3-SiO2 (CMAS) at 1·1 GPa: various amounts of K2O are added to the system, and the resulting melt compositions and temperature are extrapolated to zero K2O. The 'sandwich' experimental method was used to minimize problems caused by quench modification, and Opx and Cpx were previously synthesized at conditions near those of the melting experiments to ensure they had appropriate compositions. Results were then checked by reversal crystallization experiments. The results are in good agreement with previous work, and establish the anhydrous solidus in CMAS to be at 1320 ± 10°C at 1·1 GPa. The effect of K2O is to depress the solidus by 5·8°C/wt %, while the melt composition becomes increasingly enriched in SiO2, being quartz-normative above 4 wt % K2O. Compared with Na2O, K2O has a stronger effect in depressing the solidus and modifying melt compositions. The isobaric invariant point in the system CMAS-K2O at which Ol + Opx + Cpx + Sp + Melt is joined by sanidine (San) is at 1240 ± 10°C. During the course of the study several other isobaric invariant points were identified and their crystal and melt compositions determined in unreversed experiments: Opx + Cpx + Sp + An + Melt in the system CMAS at 1315 ± 10°C; in CMAS K2O, Opx + Cpx + Sp + An + San + Melt at 1230 ± 10°C and Opx + Sp + An + San + Sapph + Melt at 1230 ± 10°C, where An is anorthite and Sapph is sapphirine. Coexisting San plus An in three experiments help define the An-San solvus at 1230-1250°C.